Effect of Tissue Waste Fibers in the Concrete Mix on the Flexural Strength of FS 45 - Suanto, Pengki; Trisnawati, Ice (Civil Engineering Study Program Faculty of Engineering, University of Palembang, 2024)
This research aims to understand the effect of tissue waste fiber on flexural strength in concrete quality FS 45. FS 45 concrete has excellent mechanical properties under bending loads. On the other hand, in many structural applications, an enhancement in the flexural properties of concrete is needed to avoid cracking with such a high degree of bending stresses [3]. Excess tissue waste has been used as another fiber material selection because it is abundant waste, can even increase the tensile strength of the fibers, and does not damage the environment. The FS 45 concrete mixtures were obtained by blending tissue waste fibers with 0%, 0.5%, 1%, and 1.5% of the weight of cement into the mixtures in this research project. Methodology In this study, ordinary concrete beam standard samples tested in 28 days using a three-point-finding testing methodology were produced. The flexural strength of concrete with and without tissue waste fibers is tested using this test. Comparison of flexural strength value between control samples and fiber-added samples, as well as assessment of the change of mechanical strength based on percentages of fiber addition, were carried out for data analysis. The test result shows that the tissue waste fibers significantly increased the FS 45 concrete flexural strength. It results in a 15% improvement in flexural strength over fibre-free concrete at an optimum ratio of 1%. In contrast, the fibers incorporated more than 1% in terms of mass would be evenly distributed but started clumping, which leads to lower flexural strength. The study concludes that fiber from tissue waste can act as a suitable secondary reinforcement to enhance the flexural strength of concrete at proper proportions. These disclosures help recycle waste and improve concrete with new efficient parameters for use by the construction sector.